1999
DOI: 10.1523/jneurosci.19-18-07793.1999
|View full text |Cite
|
Sign up to set email alerts
|

TheDrosophilaβ-Amyloid Precursor Protein Homolog Promotes Synapse Differentiation at the Neuromuscular Junction

Abstract: Although abnormal processing of beta-amyloid precursor protein (APP) has been implicated in the pathogenic cascade leading to Alzheimer's disease, the normal function of this protein is poorly understood. To gain insight into APP function, we used a molecular-genetic approach to manipulate the structure and levels of the Drosophila APP homolog APPL. Wild-type and mutant forms of APPL were expressed in motoneurons to determine the effect of APPL at the neuromuscular junction (NMJ). We show that APPL was transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
227
1
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 249 publications
(246 citation statements)
references
References 67 publications
16
227
1
2
Order By: Relevance
“…For APPL, increased cell death is observed only when two copies of APPL are overexpressed and flies are reared at 291C (data not shown, Figure 6e-j). Because expression levels of these UAS lines are not significantly different, 23 these results demonstrate that cleavage of APPL is important for its regulation. Overexpression of APPL consistently failed to produce abnormal phenotypes (Figure 7c).…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…For APPL, increased cell death is observed only when two copies of APPL are overexpressed and flies are reared at 291C (data not shown, Figure 6e-j). Because expression levels of these UAS lines are not significantly different, 23 these results demonstrate that cleavage of APPL is important for its regulation. Overexpression of APPL consistently failed to produce abnormal phenotypes (Figure 7c).…”
mentioning
confidence: 70%
“…Torroja et al 23 reported that overexpression of wild-type and mutant forms of APPL in Drosophila motor neurons caused a dramatic increase in synaptic bouton number. Interestingly, recent studies show that synaptic bouton number in motor neuron endings was greatly increased in a Drosophila Cul-5 mutant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A null mutation of APPL exhibits behavioral deficits, which are rescued by a human APP transgene (19). Drosophila has been used to study the physiological functions of APP and APPL in synaptogenesis (20), axonal transport (21,22), and apoptosis (22). To determine whether Drosophila can be used as a model to study the molecular basis of AD pathogenesis, we examined the effects of A␤40 and A␤42 in the Drosophila brain using the GAL4-UAS system (23).…”
mentioning
confidence: 99%
“…APP was found to promote synaptogenesis in culture and is required both pre-and post-synaptically to regulate mammalian NMJ structure and function, presumably by forming a transsynaptic adhesion complex [25]. Similarly, regulation of the Drosophila APP homolog critically controls synaptic growth at the NMJ [26]. The involvement of various synaptic cell adhesion proteins in neuropsychiatric diseases indicates that abnormal synapse formation or specification may be a common risk factor for mental disorders.…”
Section: Specification and Stabilization Of The Synapse Is Mediated Bmentioning
confidence: 99%